Weathering the Inflationary Storm 2021-2022: Crisis Management Modalities for the Informal Microenterprise Sector - Zafri, Kazi Ziaul; Lertatthakornkit, Tippawan; Photchanachan, Sarana; Zhu, Tao; Wider, Walton (International Journal of Economics and Financial Issues, 2024)
Although the unforeseen shocks of the global inflation crisis of 2021-2022 rattled business practitioners, investors, and policy-makers, prior research on this phenomenon is centered on ‘mainstream’ business organizations, while the scholarly attention on informal micro-entrepreneurship businesses in the context of crisis management has been relatively sparse. This qualitative study intends to fill this gap in entrepreneurial crisis management literature by investigating the first-hand account of the adversity of the crisis and management practices as the inflation crisis unfolds. Based on semi-structured interviews and the interpretative phenomenological analysis (IPA) method with 16 informal micro-entrepreneurs from four different informal microenterprise sectors (service, trade, manufacturing, and agricultural) in Thailand, the findings revealed that this sector endured inflationary constraints related to customer base, profit margin, cash holding, and household borrowing. This study simultaneously demonstrates how informal micro-entrepreneurs bricolage responses by optimizing inventory agility and transformative supplier partnerships that shaped the immediate adjustments and doubling down on customer services, offering disruptive products and services, and digital shifting contributed to developing long-term resilient practices to navigate the inflation crisis. Furthermore, to advance our theoretical understanding for bolstering inflation crisis preparedness of micro-entrepreneurship via strategic policy responses with implications for policy-makers are also discussed.